Heart rate variability data visualizing method for elite sports - Shchedrina, Y. A.; Lutkov, V. F.; Lutkova, N. V.; Makarov, Y. M.; Tsepelevich, M. M. (Theory and Practice of Physical Culture, 2019)
The heart rate variability (HRV) data presentation tools are indispensable for the modern training and rehabilitation process management purposes since they give the means to rate the physical fitness and progress and assess contributions of the relevant bodily mechanisms. Of special importance for these purposes may be an algorithmic design of the Pythagoras tree with the tree height, inclination, color and branches (i.e. their quantity and density) indicative of the relevant test rates. Best physical fitness is described by a high, right-leaning tree with multiple and dense green branches. Based on the Pythagoras tree calculations and presentations, the coaches and athletes may take well-grounded decisions on how the further training process shall be designed and managed, with training volume, intensity and special focused rehabilitation tools. The study data shows that the higher are the athlete`s skills the more similar are the heart rate variability trees. The proposed Pythagoras tree calculation and presentation method may be used as an additional tool to effectively manage the training and rehabilitation processes in elite sports.